Periodic solutions of nonlinear differential equations with pulse influence in a banach space - Perestyuk, N. A.; Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Rank conditions for control of linear pulse systems are established. An example of control synthesis in a problem for linear pulse systems is given.